Flexibility and Social Security in Gig Workers: A Study of Gig Worker Welfare in Bandung City - Azhar Humaira Syabani; Anita Silvianita; Arry Widodo; Nurafni Rubiyanti (Formosa Journal of Multidisciplinary Research, 2024)
The development of information and digital technology has brought significant changes in the structure and way of working in various industrial sectors. One phenomenon that has emerged from these changes is the gig economy, which refers to a job market consisting of temporary or short-term contract work, where individuals or workers work as freelancers or as gig workers. This phenomenon is growing rapidly in various parts of the world, including in Indonesia. This study aims to identify the welfare of gig workers in Bandung City in terms of work flexibility and social security, and provide recommendations for policy makers to regulate a more equitable and sustainable gig economy ecosystem. The results show that work flexibility has a significant positive impact on gig workers' welfare, while social security is also important but has less influence than work flexibility. Policies that support work flexibility need to be combined with policies that provide adequate access to social security for gig workers.